2021
DOI: 10.3892/mmr.2021.11947
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide induces apoptosis in DLBCL cells by suppressing the HDACs/STAT3/Bcl‑2 pathway

Abstract: Diffuse large B-cell lymphoma (DLBCL) is a highly heterogeneous malignant tumor type, and epigenetic modifications such as acetylation or deacetylation serve vital roles in its development. Chidamide, a novel histone deacetylase inhibitor, exerts an anticancer effect against various types of cancer. The present study aimed to evaluate the cellular effect of chidamide on a number of DLBCL cell lines and to investigate its underlying mechanism. The results demonstrated that chidamide induced the death of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…LAQ824 produced anti‐proliferative, apoptosis‐related effects in DLBCL cells, associated with a reduction of the anti‐apoptotic BCL2 protein, at least in some cell lines. Similar effects were found in DLBCL cells that were incubated with chidamide, which blocks HDAC1, HDAC2, HDAC3 and HDAC10 6 (Figure 1B ), suggesting that DLBCL cells require these HDACs to survive.…”
Section: Figuresupporting
confidence: 73%
“…LAQ824 produced anti‐proliferative, apoptosis‐related effects in DLBCL cells, associated with a reduction of the anti‐apoptotic BCL2 protein, at least in some cell lines. Similar effects were found in DLBCL cells that were incubated with chidamide, which blocks HDAC1, HDAC2, HDAC3 and HDAC10 6 (Figure 1B ), suggesting that DLBCL cells require these HDACs to survive.…”
Section: Figuresupporting
confidence: 73%
“…Caspase-3 expression can correlate with increased tumor cell death in a number of cancer types. [44][45][46][47] Staining for caspase-3 was increased in the post-treatment specimens. Additionally, caspase-3 staining was significantly increased in those patients that received TVEC treatment compared with those that received radiation alone.…”
Section: Open Accessmentioning
confidence: 96%
“…It is reported that HDAC inhibitors can overcome congenital and acquired rituximab resistance in patients with B‐cell lymphoma and augment the cytotoxic activity of rituximab by upregulating the expression of CD20 in lymphoma cells. Chidamide, a new HDAC inhibitor, could be a potent therapeutic agent to treat DLBCL by inducing the DLBCL cell apoptosis by inhibiting the HDACs/STAT3/Bcl‑2 pathway 8 . Hu et al reported that chidamide combined with lenalidomide could achieved excellent outcomes in heavily pretreated aggressive DLBCL patients 9 …”
Section: Casementioning
confidence: 99%
“…Chidamide, a new HDAC inhibitor, could be a potent therapeutic agent to treat DLBCL by inducing the DLBCL cell apoptosis by inhibiting the HDACs/STAT3/Bcl‑2 pathway. 8 Hu et al reported that chidamide combined with lenalidomide could achieved excellent outcomes in heavily pretreated aggressive DLBCL patients. 9 …”
Section: Casementioning
confidence: 99%